MEASUREMENTS OF THE ROCK THERMAL PROPERTIES ON THE STANDARD CORE PLUGS AS A NECESSARY STAGE OF THE THERMALPHYSIC INVESTIGATIONS OF THE HYDROCARBON FIELDS - E. YU. Popov; R. A. Romushkevich; YU. A. Popov (Известия высших учебных заведений: Геология и разведка)
A technique of the thermal investigations of rock samples is described that provides measurements of the rock thermal conductivity, thermal diffusivity, volumetric heat capacity, and thermal anisotropy coefficient on standard core plugs (cylinders with a diameter and height of 30x30 mm) that are being used widely in laboratory oil&gas petrophysics. A theoretical basis of the anisotropic core plugs investigations is given when the principal axes of the thermal conductivity are oriented arbitrarily. The technique allows to measure the rock thermal properties and other rock properties just on the same rock samples that provides reliable data on correlations between the thermal properties and other properties. A technique important peculiarity is that the thermal property measurements on the core plugs successively saturated with the different fluids are possible. Determination of the thermal properties of the rock mineral matrix, that are necessary for the basin and hydrodynamic modeling with the modern simulators, became possible due to the technique application. The results of the thermal core plugs investigations can be used for testing of correspondence of the theoretical models of the thermal conductivity to real rock properties and for necessary theoretical model corrections estimations and their implementation in the theoretical models. It is demonstrated that application of the geometrical mean mixing law for the rock thermal conductivity prediction requires introduction of a correction factor that can be determined from the thermal measurements on the standard core plugs. Experimental estimations of the correction factors for carbonates are given. The thermal investigations of Bazhen formation rocks provided the data on the regression equations for correlations between the thermal conductivity and total organic carbon and on rock matrix thermal conductivity. Essential peculiarities of these characteristics were established for radiolarites. The data on correlations between the thermal conductivity and compressive sonic wave veiocity for dolomites are given that were obtained from the core plug collection investigations.